LATIHAN KEGEL UNTUK MENINGKATKAN KUALITAS HIDUP LANSIA - Nurrohmah, Anjar; Tri Susilowati; Annisa Andriani (P3M Universitas Aisyiyah Surakarta, 2024)
The aging process causes physical and psychological changes in a person, including weakness of the pelvic muscles resulting in urinary incontinence. The impact of urinary incontinence is that it can reduce the quality of life of the elderly due to feelings of shame and low self-esteem due to the inability to hold urine. Kegel exercises are a non-pharmacological effort to treat incontinence. The aim of Kegel exercises is to strengthen the pelvic floor muscles so that they can overcome urinary incontinence. Health promotion and education about Kegel exercises is still limited to the general public. Posyandu activities for the elderly are still limited to weighing, measuring blood pressure and regular general health checks by the Community Health Center. Therefore, it is necessary to strengthen the potential of health cadres and the elderly regarding Kegel exercises to strengthen the pelvic floor muscles. The planned solution is through health education regarding Kegel exercises for the elderly. This activity was carried out at the Posyandu for the Elderly in Sidodadi village. The target of this activity is 40 elderly people who are members of the Elderly Posyandu. Before giving the material, 5 people knew about Kegel Exercises, and 28 people did not know about Kegel Exercises. After providing the material, 21 people knew and understood how to do Kegel exercises and 13 people still did not understand Kegel exercises. This shows an increase in elderly knowledge about Kegel exercises.